PESANTREN: SANTRI, KIAI, DAN TRADISI - Ahmad Muhakamurrohman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2014)
Nowadays, there is a skeptic sense when pesantren (Islamic boarding school) is discussed. There are always the same questions; function, relevance and future guarantee for its graduates. Meanwhile, historically, pesantren became an important pillar for Indonesia education and culture. Pesantren was a traditional educational institution that has lot of roles to reach Indonesia independence in the past and educate Indonesian people. There were born many outstanding figures who became the declaratory and mover of the development of the nation. However, nowadays it seems that pesantren lost its direction and identity on facing the globalization. There are some traditions as important elements on system and curriculum that have lost. When those elements are revitalized and optimized;, hopefully its contribution will not be questioned anymore.